Volume 8: Seismic Engineering 2011
DOI: 10.1115/pvp2011-57560
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Seismic Safety Capacity of Aged Piping System: Shake Table Test on Piping Systems With Wall Thinning by E-Defense

Abstract: In order to investigate the seismic safety capacity of the piping system with local wall thinning, shake table tests on 3-D piping system models were conducted using E-Defense. Two piping system models which were the same in appearance and different in degradation condition were arranged on the shake table of E-Defense. One of the models was put into degradation condition of about 50% wall thinning at four elbows and one tee. Modified seismic motions were applied to these models at the same time. As a result, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In recent times, there has been a need for a design method that considers the plasticity and accompanying energy dissipation of the pipe to enhance the seismic design of piping systems in nuclear power plants. To date, vibration tests or analyses have shown that the response of a piping system decreases thanks to the plasticity of the pipe (Suzuki et al, 2005;Nakamura et al, 2011). However, piping analysis has been mainly based on elastic analysis, and plasticity was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, there has been a need for a design method that considers the plasticity and accompanying energy dissipation of the pipe to enhance the seismic design of piping systems in nuclear power plants. To date, vibration tests or analyses have shown that the response of a piping system decreases thanks to the plasticity of the pipe (Suzuki et al, 2005;Nakamura et al, 2011). However, piping analysis has been mainly based on elastic analysis, and plasticity was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…The elastic-plastic behavior, failure mode, and limit load were also analyzed using FEM [4,5]. Experiments have also been carried out to investigate the failure modes of major nuclear power plant piping components under cyclic loading [6], and to define the failure criteria of piping systems using the shaking table test [7]. Based on the results of these studies, the existing design methods that use linear analysis and stress-based criteria have been changed to methods that use inelastic analysis and strain-based criteria [8].…”
Section: Introductionmentioning
confidence: 99%
“…Various procedures for the safety evaluation of network systems like electric powers, roads, hospital regional systems or hospitals, bridges or strategic buildings, were proposed in literature [15][16][17][18][19][20][21][22].…”
Section: Urban Risk Assessment and Reductionmentioning
confidence: 99%